Monte Carlo study on size-dependent radiation enhancement effects of spinel ferrite nanoparticles - Bilmez, Bayram; Toker, Melis Ozsahin; Toker, Ozan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This study investigates the effect of adding spinel ferrite nanoparticles to tissues irradiated with low energy photons and simulated effect of particle size on dosimetry quantities. The simulations have been carried out with MCNP 6.2 code which enables event-by-event electron transport. Firstly, dose enhancement factors have been determined with water/ferrite mixture and for MnFe2O4, CoFe2O4, Fe3O4, NiFe2O4, ZnFe2O4, at 5,10, and 20 mgg(-1) concentrations and individual nanoparticles of Fe3O4 in a 1 cm(3) volume. Source photons used were iodine-125 spectrum and X-rays spectra with tube voltages 50 kVp, 100 kVp. The dose enhancement with 50 kVp source go as high as 1.73 with 20 mgg(-1) NP concentration, whereas with 100 kVp source, it drops to 1.13 with 5 mgg(-1). In a different simulation, an endothelial cell of tumor vasculature with nanoparticles attached to its surface has been modeled to handle the cellular level effects. The amount of self-absorption versus absorption in the cell has been compared for different particles size. Also, we presented the electron spectrum leaving the nanoparticle surfaces entering the cell volume. To achieve realistic dose enhancement for the macro scale, either high concentrations or very low photon energies are required. In the cellular scale simulations, results indicate an extraordinary difference in low energy electron spectrum, which contribute much to energy deposition within the vicinity of nanoparticles, showing the importance of targeting.
Keywords: Dose enhancement; MCNP; Monte Carlo; Particle size effect; Spinel ferrites; GOLD NANOPARTICLES; DRUG-DELIVERY; MAGNETIC NANOPARTICLES; THERAPY; RADIOTHERAPY; ENERGY; SIMULATION; DOSIMETRY; MODEL; Chemistry; Nuclear Science & Technology; Physics